A novel electrochemical sensing platform based on the esterase extracted from kidney bean for high-sensitivity determination of organophosphorus pesticides. Issue 9 (11th February 2022) - Tao, Han; Liu, Feng; Ji, Chun; Wu, Yuangen; Wang, Xiao; Shi, Qili
Abstract : An electrochemical sensing platform using kidney bean esterase as a new detection enzyme was proposed for organophosphorus pesticide determination. The determination of trichlorfon can be easily achieved with a LOD as low as 3 ng L −1 (S/N = 3). Abstract : Similar to acetylcholinesterase, the activity of plant-derived esterase can also be inhibited by organophosphorus pesticides. Therefore, an electrochemical sensing platform using kidney bean esterase as a new detection enzyme was proposed for the highly sensitive determination of organophosphorus pesticides. Purified kidney bean esterase was obtained by an efficient and economical aqueous two-phase extraction method. Carboxylated graphene/carbon nanotube composites (cCNTs–cGR) and Au nanoparticles were used to provide a biocompatible environment to immobilize kidney bean esterase and also accelerate electron transport between the analyte and the electrode surface. Due to the good synergistic electrocatalytic effects of these nanomaterials, the biosensor exhibited an amplified electrocatalytic response to the oxidation of α-naphthalenol, which makes the sensor more sensitive. Based on the inhibitory effect of trichlorfon on kidney bean esterase activity, high sensitivity and low-cost detection of trichlorfon was achieved. Under optimum conditions, the inhibition of trichlorfon is proportional to its concentration in the range of 5 to 150 ng L −1 and 150 ng L −1 to 700 ng L −1 with an ultra-low detection limit of 3 ng L −1 . Moreover, the validity of the prepared biosensor was verified by analyzing several actual agricultural products (cabbage and rice) with satisfactory recoveries ranging from 94.05% to 106.76%, indicating that kidney bean esterase is a promising enzyme source for the analysis of organophosphorus pesticides in food samples.